Tuberous sclerosis complex diagnosed from oral lesions - Araújo, Leonardo de Jesus; Muniz, Guilherme Braga; Santos, Edmilson; Ladeia, João Paulo Versiani; Martelli Júnior, Hercílio; Bonan, Paulo Rogério Ferreti (São Paulo Medical Journal, 2013)
CONTEXT: Tuberous sclerosis complex (TSC) is a genetic disease in the group known as neurocutaneous syndromes, with dominant autosomal inheritance. It is characterized by skin and adnexal lesions and central and peripheral nervous system tumors, with neurological and psychiatric findings. It may affect the heart, kidneys, eyes, face, bones, lungs, stomach and dentition. CASE REPORT: We present the case of a 66-year-old man with dermatological signs that included hypopigmented maculae, confetti-like lesions, shagreen plaque, angiofibromas on nasolabial folds, neck and back, nail dystrophy and periungual fibromas on fingers and toes. An electroencephalogram produced normal results, but magnetic resonance imaging showed a nodular image measuring 1.2 x 1.0 cm close to the Monro foramen, which was similar to cerebral parenchyma and compatible with a subependymal giant-cell astrocytoma. A conservative approach was taken, through control imaging examinations on the lesion for seven years, with absence of any expansive process or neurological symptoms. Abdominal ultrasonography revealed a solid, heterogenic and echogenic mass with a calcified focus, measuring 4.6 x 3.4 cm, in the right kidney, compatible with angiomyolipoma. The patient was treated by means of complete nephrectomy because of malignant areas seen on histopathological examination and died one month after the procedure. This case report illustrates the importance of oral clinical findings such as dental enamel pits and angiofibromas in making an early diagnosis of TSC, with subsequent screening examinations, treatment and genetic counseling.